HADES Forward Wall calibration procedure. (December 2020) - Zherebtsova, E; Morozov, S; Golubeva, M; Guber, F; Ivashkin, A
Abstract: The Forward Wall (FWall) detector is a segmented scintillation forward hodoscope with PMT readout. The FWall is one of the detector subsystems in the HADES experimental setup at SIS18 (GSI, Darmstadt, Germany) used for determination of the collision centrality and event plane orientation in nucleus-nucleus collisions. The quality of the FWall calibration is a crucial point for these tasks. The HADES experiment on particles production in Ag+Ag reaction at 1.23 and 1.58AGeV has been performed in 2019. FWall calibration was performed for both data sets. In this work the results of the FWall calibration at 1.58AGeV are presented.